Knowledge, Attitude and Compliance to Dietary Recommendation Among Type-2 Diabetes Patients Attending Medical Outpatient Clinic at the University College Hospital, Ibadan, Southwest Nigeria (African Journal of Biomedical Research, 2023)
Dietary management is important in preventing complications associated with diabetes mellitus and enhancing quality of life. However, compliance to dietary recommendations among Diabetes Patients (DPs) remain unknown. This study was designed to assess the Knowledge, Attitude and Compliance (KAC) of Type 2 diabetic patients to dietary recommendation. This cross-sectional study involved 101 DPs attending Medical Outpatient Clinic at University College Hospital, Ibadan, Nigeria. A semi-structured, interviewer-administered questionnaire was used to obtain information on socio-demographic characteristics, diabetes history and KAC to dietary recommendation. Knowledge was assessed on a 26-point scale and categorized as good (≥18.0) and poor (